Systematic Literature Review on Community Empowerment in Preventing Stunting in Children: Challenges and Impacts - Kemal, Taufik; Iip Permana (Journal of Educational Management Research, 2025)
This study aims to identify strategies, barriers, and the impact of community empowerment on stunting prevention and provide recommendations for strengthening community-based programs. The method employed was a Systematic Literature Review (SLR) of scientific publications from 2018 to 2025, obtained through Google Scholar, with strict selection based on inclusion and exclusion criteria. The analysis results indicate that community empowerment is carried out through three stages: building awareness, increasing capacity, and facilitating independence. Activities include nutrition education, childcare training, yard utilisation, and the formation of local food business groups. The main obstacles faced were low community participation, limited facilities, and socio-cultural constraints. Positive impacts include increased nutritional knowledge, improved healthy lifestyles, and family economic independence. This study emphasises the importance of educational management in the success of the empowerment program. Relevant curriculum management, ongoing training, and data-driven evaluation are key to increasing community capacity and ensuring program sustainability. Cross-sector collaboration and a locally focused, potential-based approach are necessary for achieving long-term benefits.